Molecular Characterization of Human Lymph Node Stromal Cells During the Earliest Phases of Rheumatoid Arthritis - Karouzakis, Emmanuel; Hähnlein, Janine; Grasso, Cristoforo; Semmelink, Johanna F.; Tak, Paul P.; Gerlag, Danielle M.; Gay, Steffen; Ospelt, Caroline; van Baarsen, Lisa G. M. (Frontiers in Immunology, 2019)
Rheumatoid arthritis (RA) is a progressive, destructive autoimmune arthritis. Break of tolerance and formation of autoantibodies occur years before arthritis. Adaptive immunity is initiated in lymphoid tissue where lymph node stromal cells (LNSCs) play a crucial role in shaping the immune response and maintaining peripheral tolerance. Here we performed the first epigenomic characterization of LNSCs during health and early RA, by analyzing their transcriptome and DNA methylome in LNSCs isolated from lymph node needle biopsies obtained from healthy controls (HC), autoantibody positive RA-risk individuals and patients with established RA. Of interest, LNSCs from RA-risk individuals and RA patients revealed a common significantly differential expressed gene signature compared with HC LNSCs. Pathway analysis of this common signature showed, among others, significant enrichment of pathways affecting the extracellular matrix (ECM), cholesterol biosynthesis and immune system. In a gel contraction assay LNSCs from RA-risk individuals and RA patients showed impaired collagen contraction compared to healthy LNSCs. In RA LNSCs a significant enrichment was observed for genes involved in cytokine signaling, hemostasis and packaging of telomere ends. In contrast, in RA-risk LNSCs pathways in cancer (cell cycle related genes) were differentially expressed compared with HC, which could be validated in vitro using a proliferation assay, which indicated a slower proliferation rate. DNA methylation analyses revealed common and specific differentially methylated CpG sites (DMS) in LNSC from RA patients and RA-risk individuals compared with HC. Intriguingly, shared DMS were all associated with antigen processing and presentation. This data point towards alterations in cytoskeleton and antigen-processing and presentation in LNSC from RA-risk individuals and RA patients. Further studies are required to investigate the consequence of this LNSC abnormality on LNSC-mediated immunomodulation.